2011
DOI: 10.1111/j.1472-765x.2011.03073.x
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the DNA repair protein, Rad23 from kuruma shrimp Marsupenaeus japonicus: full-length cDNA cloning and characterization

Abstract: Aims:  Lesions of DNA are removed by nucleotide excision repair (NER) process in the living systems. NER process‐related host factors are believed to aid recovery steps during viral integration. Here, we report identification and characterization of a DNA repair molecule Rad23 from kuruma shrimp Marsupenaeus japonicus. Methods and Results:  The full‐length cDNA of M. japonicus Rad23 gene (MjRad23) has 1149 bp coding for a putative protein of 382 amino acids with a 5′ untranslated region (UTR) of 92 bp and 3′ U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Following WSSV viral infection in shrimp, it functions as a suppressor protein. Thus, it provides the virus greater chance of viral replication and dissemination (Flegel 2007;He et al 2009;Sudhakaran et al 2011). According to Wang et al (2005), an increased expression of ubiquitin conjugating enzyme in P. vannamei (PvUbc) was detected in a time course study by real-time PCR as well as RT PCR and reported that RING H2 protein WSSV 249 from WSSV may function as E3 ligase by sequestering PvUbc for viral pathogenesis in shrimp.…”
Section: Discussionmentioning
confidence: 98%
“…Following WSSV viral infection in shrimp, it functions as a suppressor protein. Thus, it provides the virus greater chance of viral replication and dissemination (Flegel 2007;He et al 2009;Sudhakaran et al 2011). According to Wang et al (2005), an increased expression of ubiquitin conjugating enzyme in P. vannamei (PvUbc) was detected in a time course study by real-time PCR as well as RT PCR and reported that RING H2 protein WSSV 249 from WSSV may function as E3 ligase by sequestering PvUbc for viral pathogenesis in shrimp.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, homologies between invertebrates and DNA repair proteins from a diverse array of organisms from protists to mammals have been reported ( e.g . p53, RAD23) . As an example, the protein FANCD2 associated with the human NER repair‐deficient disease, Fanconi anemia, has been found to be a paralog to sea urchin FANDCD2 .…”
Section: Ecological Aspects Of Uvr‐induced Dna Damage and Repairmentioning
confidence: 99%
“…Nucleotide excision repair (NER) is generally regarded to be a very important pathway for repair of UV‐induced DNA damage in both prokaryotes and eukaryotes, and generally includes damage recognition, incision, excision, repair synthesis, and ligation (Xie, Liu, Zhang, & Wang, ). Some proteins related to NER have been identified in Bombyx mori , including radiation sensitive 4 (RAD4), a key DNA repair protein that recognize various types of DNA damage (Burns, Guzder, Sung, Prakash, & Prakash, ; Chen et al, ; Gillet & Schärer, ; Jansen, Verhage, & Brouwer, ; Sinha & Häder, ; Sudhakaran et al, ; Xu, Xu, Wang, He, & Kawasaki, ). A Rad4 mutant in yeast was found to be highly sensitive to UV radiation and completely defective in NER (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%